2017
DOI: 10.1182/blood-2016-09-741629
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 modulates regulatory T-cell homeostasis during low-dose interleukin-2 therapy

Abstract: Key Points IL-2 induces expression of PD-1 on Tregs, and PD-1 blockade promotes Treg differentiation and apoptosis. PD-1 regulates IL-2–induced Treg proliferation and prolongs Treg survival in murine models and in patients receiving low-dose IL-2 therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 59 publications
4
125
0
Order By: Relevance
“…The PD‐1/PD‐L1 axis might regulate the activation of naïve Treg by APC, and thus anti‐PD‐1 treatment could affect the induction of these cells. In the IL‐2‐induced chronic graft‐versus‐host disease (cGVHD) mouse model, concomitant administration of low‐dose IL‐2 and anti‐PD‐1 antibody has been found to induce an increase in peripheral blood Treg and amelioration of cGVHD in 1 week . Consistent with this, we observed that the proportion of peripheral blood effector Treg after 2 courses of anti‐PD‐1 therapy in the present study also increased.…”
Section: Discussionsupporting
confidence: 88%
“…The PD‐1/PD‐L1 axis might regulate the activation of naïve Treg by APC, and thus anti‐PD‐1 treatment could affect the induction of these cells. In the IL‐2‐induced chronic graft‐versus‐host disease (cGVHD) mouse model, concomitant administration of low‐dose IL‐2 and anti‐PD‐1 antibody has been found to induce an increase in peripheral blood Treg and amelioration of cGVHD in 1 week . Consistent with this, we observed that the proportion of peripheral blood effector Treg after 2 courses of anti‐PD‐1 therapy in the present study also increased.…”
Section: Discussionsupporting
confidence: 88%
“…PD1 plays a crucial role in Treg cell homeostasis and survival as IL‐2 stimulation with PD1 blockade or genetic deletion of PD1 resulted in an overt proliferation of Treg cells followed by a rapid contraction due to increased apoptosis . A recent study reported that apoptotic intratumoral Treg cells express a low level of PD1 (PD1 lo ) whereas viable intratumoral Treg cells showed enhanced PD1 expression (PD1 hi ).…”
Section: Inhibitory Receptorsmentioning
confidence: 99%
“…We recently demonstrated that PD-1 is a critical homeostatic regulator for Treg by modulating proliferation and apoptosis during IL-2 therapy [39]. This study showed that exogenous IL-2 promptly induces the expression of PD-1 particularly on central-memory Tregs and increased PD-1 expression was maintained during IL-2 therapy.…”
Section: Low-dose Il-2 Combined With Checkpoint Blockadementioning
confidence: 68%